Analysis Of Factors Affecting Tourist Visits At Dolok Oan Dili Beach, Timor Leste - Apolinario Valentim Dos Santos; Ida Ayu Komang Juniasih; Ida Bagus Radendra Suastama; Ida Ayu Trisna Wijayanthi; Ni Nyoman Menuh (Cita konsultindo, 2024)
Dolok Oan Beach is a very beautiful beach and is one of the tourist attractions in downtown Dili. The research objective was to analyze the factors that influence tourist visits to Dolok Oan Dili Beach, Timor Leste. The research was carried out purposively (purposive sampling) at the Dolok Oan Beach tourist attraction in Dili, Timor Leste. The sampling method is accidental sampling, namely sampling based on sheer coincidence, which is taken as many as 100 people. The data series technique used is the questionnaire approach. The outcomes of the observe shows that: a) The profits thing has a high quality and large have an effect on at the number of vacationer visits. this means that elevated attention to income will lead to an growth in the number of traveller visits, b) tour expenses have a terrible and extensive effect at the variety of tourist visits. this means that expanded attention to tour prices will result in a lower inside the number of traveller visits, c) tour time has a negative and tremendous impact on the wide variety of traveller visits. which means that improved interest to tour time will lead to a lower within the wide variety of tourist visits, d) centers have a high quality and full-size influence at the range of traveler visits. because of this accelerated attention to centers will cause an increase in the range of visitor visits, and e) earnings, travel fees, travel time and centers concurrently have a giant effect on the range of vacationer visits.